IMPROVING THE EFFICIENCY OF PROFESSIONAL ACTIVITY BY MEANS OF MODERN MULTIMEDIA TECHNOLOGIES - Harpul, Oksana; Pylypiv, Volodymyr; Lutsyk, Mariia (Mountain School of Ukrainian Carpaty, 2021)
Ukraine is currently reforming its education system to bring it closer to modern social and economic realities. One of the key areas is to prepare future teachers for the knowledge of multimedia technologies, as they should lay the foundation for computer training of students and form the basic ideas and skills in the field of multimedia. The article shows the possibilities of effective use of multimedia for the implementation of educational and developmental functions of education in secondary school in the context of digitalization of education. The current state of use of multimedia technologies in the professional activity of a teacher is analyzed; features of studying the topic "Multimedia technologies" in the senior classes of the profile school; examples of using multimedia services to create interactive exercises and tasks are given; developed a site with guidelines for the use of multimedia technologies in professional activities for subject teachers; The results of approbation are given, which show that multimedia technologies open new methodological approaches in the system of general education, allow to save lesson time, fill it with information, combining various tools that will promote deeper and more conscious assimilation of educational material. Thus, interactivity, structuring and visualization of information increases the motivation of students, activates their cognitive activity. Summarizing the results of the survey, it can be argued that multimedia technologies open up new methodological approaches in the general education system, save time, fill the lesson with information, and combine various tools that will promote deeper and more conscious learning. Thus, interactivity, structuring and visualization of information increases the motivation of students, activates their cognitive activity.